Analysing digital marketing strategies to enhance brand awareness: A case study of Ichyo Crepes - micro, small, and medium enterprise (MSME) - Leoni Fitria Suryawati Dewi; I Made Widiantara; Majid Wajdi; Norhayati Mohd Yusof; QingHao Wu; Yuen Fook Chan (Journal of Commerce, Management, and Tourism Studies, 2026)
This study aims to analyse the effectiveness of digital marketing strategies in enhancing the brand awareness of Ichyo Crepes, a Micro, Small, and Medium Enterprise (MSME). The research employed a descriptive qualitative approach using a case study design. Data were collected through direct observation, in-depth interviews with the business owner, and documentation study, including social media content, digital promotional materials, and other supporting records. The data were analysed using the interactive model of qualitative data analysis, consisting of data reduction, data display, and conclusion drawing and verification. The findings indicate that the implementation of digital marketing strategies through social media platforms, engaging visual content, interactive promotional activities, and the utilization of customer reviews has significantly increased brand exposure and expanded the business's market reach. Furthermore, consistent content publication and active engagement with customers have strengthened brand recognition and enhanced consumer trust in Ichyo Crepes' products. However, the effectiveness of these strategies remains constrained by limited human resources, inconsistent digital media management, and intense competition within the same industry. The study concludes that a well-planned, consistent, and customer-oriented digital marketing strategy contributes positively to strengthening brand awareness and improving the competitive advantage of Ichyo Crepes in the increasingly competitive digital marketplace. The findings also provide practical insights for MSMEs seeking to optimize digital marketing initiatives to improve brand visibility and sustain business growth.